Metallothionein is elevated in liver and duodenum of Atp7b(−/−) mice - Zhang-Hagenlocher, Christine; Volkmann, Martin; Tuma-Kellner, Sabine; Stremmel, Wolfgang; Merle, Uta (BioMetals, 2018)
Different mutations in the copper transporter gene Atp7b are identified as the primary cause of Wilson’s disease. These changes result in high copper concentrations especially in the liver and brain, and consequently lead to a dysfunction of these organs. The Atp7(−/−) mouse is an established animal model for Wilson’s disease and characterized by an abnormal copper accumulation, a low serum oxidase activity and an increased copper excretion in urine. Metallothionein (MT) proteins are low molecular weight metal-binding proteins and essential for the zinc homeostasis but also play a role for the regulation of other metals, e.g. copper. However the molecular mechanisms of MT in regard to Atp7b remain still elusive. In this study we investigate the expression of MT in the liver and duodenum of Atp7b(−/−) mice and wildtype mice. Hepatic and duodenal expression of MT was measured by real-time reverse transcription-polymerase chain reaction and post-translational expression was analyzed by immunoblot and immunofluorescence. Expression of MT in liver und duodenum was significantly higher in Atp7b(−/−) mice than in controls. Hepatic and duodenal copper, iron and zinc content were also studied. Compared to control hepatic copper and iron content was significantly higher while hepatic zinc content was significantly lower in Atp7b(−/−) mice. In the duodenum copper and zinc content of Atp7b(−/−) mice was significantly lower than in controls. Duodenal iron content was also lower in Atp7b(−/−) mice, but did not reach statistical significance. The results of our study suggest that metallothionein is elevated in the liver and duodenum of Atp7b(−/−) mice.